Logika Estetik 'Keong Racun' di Tengah Masyarakat Konsumerisme - Riwayanto, Doni (Ekspresi, 2010)
The Logic of Keong Racun Aesthetic in Consumerism. Shinta and Jojo are two teenagers who live in a true hyper-real world, more hyper-real than Baudrillard ahs ever imagined that is exemplified in his simulation strategy. They are more hyper-real than the Disneyland, the world which Umberto Eco thinks is the most hyper-real thing in the world. In their world, Shinta and Jojo get their existence by uploading their video of Keong Racun song lip-sync (lip-synchronization). Those two girls are not the composers nor the real singers of the song, however what they have done was grasped as a differentsignifer/signifedby the others. Even it is interpreted as other signified in this paper; namely as a real manifestation of the true postmodern aesthetic. Keywords: Keong racun, Shinta-Jojo, Boudrillard.